Overview of the CLEF-2006 Cross-Language Speech Retrieval Track - Oard, Douglas W.; Wang, Jianqiang; Jones, Gareth J.F.; White, Ryen W.; Pecina, Pavel; Soergel, Dagobert; Huang, Xiaoli; Shafran, Izhak (Cross-Language Evaluation Forum (CLEF 2006), Alicante, Spain, 2006)
The CLEF-2006 Cross-Language Speech Retrieval (CL-SR) track included two tasks: to identify topically coherent segments of English interviews in a known-boundary condition, and to identify time stamps marking the beginning of topically relevant passages in Czech interviews in an unknown-boundary condition. Five teams participated in the English evaluation, performing both monolingual and cross-language searches of ASR transcripts, automatically generated metadata, and manually generated metadata. Results indicate that the 2006 evaluation topics are more challenging than those used in 2005, but that cross-language searching continued to pose no unusual challenges when compared with collections of character-coded text. Three teams participated in the Czech evaluation, but no team achieved results comparable to those obtained with English interviews. The reasons for this outcome are not yet clear.